THE CHANGING LANDSCAPE OF PUNJABI CULTURE IN THE ERA OF GLOBALISATION - Singh, Harmeet (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Globalisation has changed the cultural identities of nearly all countries, and with that, the Punjabi culture of Punjab, which lies in Northwest India and Northeast Pakistan. How globalisation has altered some features of Punjabi culture, particularly language, music, traditional customs, and the scope of Punjabi diasporic influence is the main concern of this paper. The paper analyses, through quantitative and qualitative approaches, secondary data, such as scholarly works, media, and cultural artefacts, to illustrate the dual effect of globalisation through which Punjabi music and diaspora communities have gained greater global reach and cultural confidence while simultaneously traditional customs and the Punjabi language have suffered erosion as a result of western influence and internal migration. It is found that while globalisation offers pathways for multi–cultural interactions, it poses challenges in preserving “authentic” Punjabi culture, necessitating the use of adaptation strategies to achieve cultural cohesion.